STRATEGI PEMERINTAH INDONESIA UNTUK MENINGKATKAN DAYA SAING SEKTOR PENERBANGAN PASCA BERLAKUNYA KEBIJAKAN ASEAN SINGLE AVIATION MARKET PERIODE TAHUN 2015-2017 - Ilham Zhafran Purnawan, - (2018)
This research aims to understand how Indonesia crafting a strategy to increase the competitiveness of the sector of services were facing competition in the commercial aviation liberalization in ASEAN, ASEAN Single Aviation Market, in the period 2015-2017. The method in this research uses qualitative research methods. While technical data collection and information use studies library, where the technical assessment done by searching the data and facts from sources of books, articles and journals, websites, as well as documents relating to the issue research. The study also uses the base framework of thinking that is directly related to the problem that happens, Theories, concepts, Strategy Regionalism concept of competitive advantage, the concept of foreign policy, and the concept of ASEAN Single Aviation Market. ASEAN Single Aviation Market is a policy of free trade in air transport services which requires every aviation industry member countries to compete and minimizes government intervention. The results showed that, overall, Indonesia has to fix its domestic aviation sector. Although the aviation business is ready, but industry supporters such as airport management and the role of the national aviation authority is still far behind compared to other ASEAN countries